The Mammalian Locus Coeruleus Complex—Consistencies and Variances in Nuclear Organization - Paul R. Manger; Oxana Eschenko (Brain Sciences, 2021)
Descriptions of the nuclear parcellation of the locus coeruleus complex have been provided in approximately 80 mammal species spanning the phylogenetic breadth of this class. Within the mammalian rostral hindbrain, noradrenergic neurons (revealed with tyrosine hydroxylase and dopamine-ß-hydroxylase immunohistochemistry) have been observed within the periventricular grey matter (A4 and A6 nuclei) and parvicellular reticular nucleus (A5 and A7 nuclei), with the one exception to date being the tree pangolin, where no A4/A6 neurons are observed. The alphanumeric nomenclature system, developed in laboratory rodent brains, has been adapted to cover the variation observed across species. Cross-species homology is observed regarding the nuclear organization of noradrenergic neurons located in the parvicellular reticular nucleus (A5 and A7). In contrast, significant variations are observed in the organization of the A6 neurons of the locus coeruleus proper. In most mammals, the A6 is comprised of a moderate density of neurons, but in Murid rodents, primates, and megachiropteran bats, the A6 exhibits a very high density of neurons. In primates and megachiropterans, there is an additional moderate density of A6 neurons located rostromedial to the high-density portion. These variations are of importance in understanding the translation of findings in laboratory rodents to humans.